Novel voltammetric responses of a 1,1 '-ferrocene bis(methylene aza-18-crown-6) receptor to group 1 and 2 metal cations in acetonitrile - Chen, Z; Pilgrim, A; Beer, P (1998)
A 1,1′-ferrocene bis(methylene aza-18-crown-6) ligand (L) and its inclusion complexes with Na+, K+, Ba2+ and Mg2+ are studied in acetonitrile by cyclic and square wave voltammetry. The ligand-metal complex stoichiometry is found to vary from 1:1 to 1:2 with increasing concentration of the metal cation. There is also a binding selectivity for dications over monocations. Simultaneous addition of Mg2+ and Ba2+ gives rise to a novel voltammetric feature which is rationalised by the formation of three different species; the symmetrical homobimetallic complexes, L-2Ba2+ and L-2Mg2+, and the asymmetrical heterobimetallic complex, L-Ba2+-Mg2+. L is therefore a redox active receptor capable of the simultaneous electrochemical recognition of different metal cations. An electrostatic model is proposed to account for the observed changes in the mean potential of L upon cation complexation. © 1998 Elsevier Science S.A. All rights reserved.